Opposite macroevolutionary responses to environmental changes in grasses and insects during the Neogene grassland expansion - Gael J. Kergoat (Nature Portfolio, 2018)
The expansion of grassland plant diversity is thought to have facilitated diversification of herbivorous insects. Here, the authors show opposing evolutionary dynamics in a clade of African grasses and associated stemborers, opposing the hypothesis about grasslands as a 'cradle' of herbivore diversity.